A Semiotic Theory of Language - Shaumyan, Sebastian (Indiana University Press, 1987)
Taking issue with Transformational Grammar Theory, which has dominated language study since Noam Chomsky introduced it more than thirty years ago, Sebastian Shaumyan separates language from psychology, arguing that language occupies a different world, that of the semiotic. The author develops a unique theory based on an analysis of the semiotic properties of language, which he names applicative grammar. This theory is then used to distinguish two levels of grammar and outline a comprehensive semiotic theory of language.